Diagnostic Accuracies of Glycated Hemoglobin, Fructosamine, and Homeostasis Model Assessment of Insulin Resistance in Predicting Impaired Fasting Glucose, Impaired Glucose Tolerance, or New Onset Diabetes After Transplantation - Rosettenstein, K.; Viecelli, A.; Yong, K.; Nguyen, H.; Chakera, Aron; Chan, D.; Dogra, G.; Lim, E.; Wong, G.; Lim, W. (2015)
© 2015 Wolters Kluwer Health, Inc. All rights reserved. BACKGROUND: New onset diabetes after transplantation (NODAT) is associated with a 3-fold greater risk of cardiovascular disease events, with early identification and treatment potentially attenuating this risk. The optimal screening test to identify those with NODAT remains unclear, and the aim of this study was to examine the diagnostic accuracies of 4 screening tests in identifying impaired fasting glucose, impaired glucose tolerance (IGT), and NODAT. METHODS: This is a single-center prospective cohort study of 83 nondiabetic kidney transplant recipients between 2008 and 2011. Oral glucose tolerance test was considered the gold standard in identifying IFG/IGT or NODAT. Diagnostic accuracies of random blood glucose, glycated hemoglobin (HBA1c), fructosamine, and Homeostasis Model Assessment-Insulin Resistance in predicting IFG/IGT or NODAT were assessed using the area under the receiver operating characteristic curve. RESULTS: Forty (48%) recipients had IFG/IGT or NODAT. Compared with HBA1c with adjusted area under the curve (AUC) of 0.88 (95% confidence interval [95% CI], 0.77-0.93), fructosamine was the most accurate test with adjusted AUC of 0.92 (95% CI, 0.83-0.96). The adjusted AUCs of random blood glucose and Homeostasis Model Assessment-Insulin Resistance in identifying IFG/IGT were between 0.81 and 0.85. Restricting to identifying IGT/NODAT using 2-hour oral glucose tolerance test (n = 66), fructosamine was the most accurate diagnostic test with adjusted AUC of 0.93 (95% CI, 0.84-0.99), but not statistically different to HBA1c with adjusted AUC of 0.88 (95% CI, 0.76-0.96). CONCLUSIONS: Although HBA1c is an acceptable and widely used screening test in detecting IFG/IGT or NODAT, fructosamine may be a more accurate diagnostic test but this needs to be further examined in larger cohorts.